THE EFFORTS OF NATO TO FIGHT TERRORISM IN AFGHANISTAN POST SEPTEMBER 11, 2001 - Janitra Yaneswari Tanjung P (2011)
This undergraduate thesis attempts to elaborate the efforts of NATO in Afghanistan in running their missions to counter terrorism after the tragically moment of buildings' bombings (WTC and Pentagon) in 11 September, 2001 in the United States of America. NATO as an international organization wants to eradicate terrorist networks with doing some military actions, particularly in Afghanistan. Afghanistan as one of counter terrorism area assumed as the largest base for terrorist training, espe